TEACHER PERFORMANCE BASED ON PRINCIPAL LEADERSHIP, COMMITMENT TEACHER, AND CULTURE SCHOOL (Study at SMA Batik 2 Surakarta) - Ekasari, Efi; Mursito, Bambang; Pawenang, Supawi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This article aims to prove the relationship between the principal’s leadership, teacher’s competence, school culture, and teacher’s performance at SMA Batik 2 Surakarta. This research is quantitative or research by using a quantitative approach. The research method is in the form of survey research using quantitative research with a sample size of about 20 teachers. The data collection method used a questionnaire with a saturated sampling technique. The data were collected using an instrument that had been validated and which was reliable. Processing of data using the SPSS program using multiple regression equation analysis tools, F test, t-test, and the coefficient of determination. The results of the data analysis showed there is positive and very significant influence of the principal’s leadership, teacher’s competence, and school cultures on the teachers’ performance with the percentage of 77 %, there is positive and very significant influence of the of principal’s leadership on the teacher’s performance, there is positive and very significant influence of teacher’s competence on the teachers’ performance and there is positive and very significant influence of school culture on the teachers’ performance. Keywords: principal’s leadership, teacher’s competence, school culture and teacher’s performance